(untitled) - Avgerou, Chrisanthi (London, 1993)
This book provides comprehensive description and critical discussion of the processes of information systems development and management. It is suitable as an introductory text for courses delicated to the study of information systems. It is also suitable for courses in information management, as a complement to texts which elaborate on information technology topics
Keywords: Information storage and retrieval systems